A Real-Time Fuzzy Load Flow and Contingency Analysis Based on Gaussian Distribution System (Journal of Engineering, 2015)
Fuzzy logic is used to solve the load flow and contingency analysis problems, so decreasing computing time and its the best selection instead of the traditional methods. The proposed  method is very accurate with outstanding computation time, which made the fuzzy load flow (FLF) suitable for real time application for small- as well as large-scale power systems. In addition that, the FLF efficiently able to solve load flow problem of ill-conditioned power systems and contingency analysis. The FLF method using Gaussian membership function requires less number of iterations and less computing time than that required in the FLF method using triangular membership function. Using sparsity technique for the input Ybus sparse matrix data gives reduction in overall computation time and storage requirements. The performance of the used methods had been tested on two typical test systems being the IEEE 14-bus and 30-bus systems in addition to the 362-bus Iraqi National Grid. All the obtained results under normal operating conditions show that the computation time of the fuzzy Load Flow (FLF) is less than the fast decoupled load flow (FDLF).